2013
DOI: 10.1071/an12168
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and productive response to suckling restriction and dietary flushing in primiparous grazing beef cows

Abstract: The objectives of the present experiment were to analyse the reproductive and productive responses to suckling-restriction treatments and flushing in primiparous grazing beef cows. During 3 years, 153 primiparous anoestrus cows were assigned randomly to one of four treatments in a 2 by 2 factorial arrangement of suckling-management treatments and flushing. Suckling-restriction treatments started at 61 ± 10 days postpartum and consisted of applying nose plates to calves for 12 days (i.e. TS treatment) or 5 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…The effect of the pre-mating supplementation on BCS is not consistent and seems to depend, at least partially, on the supplement used. Astessiano et al (2013) and Soca et al (2013) used a supplement based on whole rice bran and reported no effect on BCS. However, cows grazing on pasture improved with Lotus subbiflorus cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the pre-mating supplementation on BCS is not consistent and seems to depend, at least partially, on the supplement used. Astessiano et al (2013) and Soca et al (2013) used a supplement based on whole rice bran and reported no effect on BCS. However, cows grazing on pasture improved with Lotus subbiflorus cv.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term supplementations before or during the mating period, with or without association with temporary weaning, are alternatives to increase pregnancy rates in cows with sub-optimal BCS (Pérez-Clariget et al, 2007;Soca et al, 2013). The supplement most frequently used in these studies has been whole rice bran, an energy nutrient with 130-180 g kg −1 of crude protein (CP) (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in grazing production systems dairy and beef cows with better BCS during the pre and postpartum periods, or with better BCS at calving, had an earlier first postpartum ovulation (Meikle et al, 2004a;Quintans et al, 2010;Soca et al, 2013b). Soca et al (2013b) determined that the length from calving to first ovulation in beef cows decreased by 49 days for each incremental unit of improvement of BCS at calving (scale 1 to 8). Stagg et al (1995) reported a prolonged period of anestrus in cows with poor body condition.…”
Section: Follicular and Luteal Function And Physiology Of The Reprodumentioning
confidence: 99%
“…Extensive beef cow-calf production systems depend on the quantity and quality of grazed forages to meet their nutritional demands throughout the year. In temperate environments, nutrient availability of grazed forages fluctuates during seasons (13, 42), and often, in spring-calved beef cows, the lowest nutrient availability occurs during pregnancy in winter, and cows lose body tissue to support conceptus growth (13,37,42).…”
mentioning
confidence: 99%
“…Extensive beef cow-calf production systems depend on the quantity and quality of grazed forages to meet their nutritional demands throughout the year. In temperate environments, nutrient availability of grazed forages fluctuates during seasons (13, 42), and often, in spring-calved beef cows, the lowest nutrient availability occurs during pregnancy in winter, and cows lose body tissue to support conceptus growth (13,37,42).Microarray technology has been used to evaluate hepatic metabolic adaptations to pregnancy (19), transition period, early and midlactation (1, 25, 28), negative energy balance (NEB) or dietary restriction (1,26,29), and transition-related metabolic diseases (27) in dairy cows. In is well known that dairy and beef cows have been selected for different purposes and consequently, they have developed different metabolic adaptation strategies (47, 51).…”
mentioning
confidence: 99%